Characterization of Frond and Flower Development and Identification of FT and FD Genes From Duckweed Lemna aequinoctialis Nd - Yoshida, Akiko; Taoka, Ken-ichiro; Hosaka, Aoi; Tanaka, Keisuke; Kobayashi, Hisato; Muranaka, Tomoaki; Toyooka, Kiminori; Oyama, Tokitaka; Tsuji, Hiroyuki (Frontiers in Plant Science, 2021)
Duckweeds (Araceae: Lemnoideae) are aquatic monocotyledonous plants that are characterized by their small size, rapid growth and wide distribution. Developmental processes regulating the formation of their small leaf-like structures, called fronds, and tiny flowers are not well characterized. In many plant species, flowering is promoted by the florigen activation complex, whose major components are florigen FT protein and transcription factor FD protein. How this complex is regulated at the molecular level during duckweed flowering is also not well understood. In this study, we characterized the course of developmental changes during frond development and flower formation in Lemna aequinoctialis Nd, a short-day plant. Detailed observations of frond and flower development revealed that cell proliferation in the early stages of frond development is active as can be seen in the separate regions corresponding to two budding pouches in the proximal region of the mother frond. L. aequinoctialis produces two stamens of different lengths with the longer stamen growing more rapidly. Using high-throughput RNA sequencing (RNA-seq) and de novo assembly of transcripts from plants induced to flower, we identified the L. aequinoctialis FT and FD genes, whose products in other angiosperms form a transcriptional complex to promote flowering. We characterized the protein-protein interaction of duckweed FT and FD in yeast and examined the functions of the two gene products by overexpression in Arabidopsis. We found that L. aequinoctialis FTL1 promotes flowering, whereas FTL2 suppresses flowering.